Islamic Financial Literacy and Regulatory Framework in the Implementation of Equity Crowdfunding in Indonesia - Maieva Wulan Dari; Raden Arfan Rifqiawan (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2025)
Sharia investment through Equity Crowdfunding (ECF) has become one of the main pillars in developing the Islamic financial system in Indonesia. Although it is regulated by OJK Regulation No. 57/POJK.04/2020 and strengthened by the DSN-MUI fatwa, the implementation of Sharia-compliant ECF still faces significant challenges. This study aims to analyse the legal framework of Sharia ECF in Indonesia, evaluate compliance with its principles in its practices, and identify challenges related to financial literacy and legal protection for investors and issuers. The research method used is a normative legal approach with qualitative analysis through a literature review of relevant regulations, fatwas, and legal documents. The findings show that the low level of financial literacy and inadequate supervision of ECF platforms affect investor participation and the effectiveness ..of legal protection. Based on these findings, the study recommends the massive enhancement of financial literacy, strengthening Sharia-based supervision, and developing Sharia dispute resolution mechanisms to create a fair, sustainable, and inclusive Islamic capital market.Keywords: Equity Crowdfunding; Islamic Investment; Financial Literacy; Regulation.